Systematic review of active surveillance versus surgical management of asymptomatic small non‐functioning pancreatic neuroendocrine neoplasms. Issue 1 (5th October 2016) - Partelli, S.; Cirocchi, R.; Crippa, S.; Cardinali, L.; Fendrich, V.; Bartsch, D. K.; Falconi, M.
Abstract: Background: The incidence of asymptomatic, sporadic, small non‐functioning pancreatic neuroendocrine neoplasms (NF‐PNENs) has increased in recent decades. Conservative treatment has been advocated for these tumours. The aim of this study was systematically to evaluate the literature on active surveillance and to compare this with surgical management for asymptomatic sporadic small NF‐PNENs. Methods: PubMed, Embase and the Cochrane Library were searched systematically for studies that compared the active surveillance of asymptomatic, sporadic, small NF‐PNENs with surgical management. PRISMA guidelines for systematic reviews were followed. Results: After screening 3915 records, five retrospective studies with a total of 540 patients were included. Of these, 327 patients (60·6 per cent) underwent active surveillance and 213 (39·4 per cent) had surgery. There was wide variation in the tumour diameter threshold considered as inclusion criterion (2 cm to any size). The median length of follow‐up ranged from 28 to 45 months. Measurable tumour growth was observed in 0–51·0 per cent of patients. Overall, 46 patients (14·1 per cent) underwent pancreatic resection after initial conservative treatment. In most patients the reason was an increase in tumour size (19 of 46). There were no disease‐related deaths in the active surveillance group in any of the studies. Conclusion: This systematic review suggests that active surveillance of patients affected by sporadic, small, asymptomatic NF‐PNENs may be a good alternative to surgical treatment. Abstract : Watch and wait is safe